6) 28-(3c+4) =2 (c+6)+c
When there is a - in front of an expression in parentheses , change the sign of each term of the expression.
28-3c-4=2(c+6)+c
Distribute 2 through the parentheses
28-3c-4=2c+12+c
Now we do the same thing only different way
2(c+6)
Multiply each term in the parentheses by 2
2c+2×6
Multiply the numbers
2c+12
_____________
28-3c-4=2c+12+c
subtract the numbers
24-3c=2c+12+c
Collect like terms
24-3c=3c+12
It's the same thing only different way ok
2c+c
If a term doesn't have a coefficient , it is considered that the coefficient is 1.
2c+1c
Collect like terms by adding their coefficients
(2+1)c
Add the numbers
3c
________
24-3c=3c+12
Move variable to the left hand side and change its sign
24-3c-3c=12
Move constant to the right by adding its opposite to both sides
-3c-3c+24-24=12-24
eliminate the opposites
-3c-3c=12-24
Collect like terms
-6c=12-24
Calculate the difference
-6c=-12
so the same thing only different way ok
12-24
Keep the sign of the number with the larger absolute value and subtract the smaller absolute value from the larger.
-(24-12)
Subtract the numbers
-12
__________
-6c=-12
divide both sides of the equation by -6
-6c÷(-6)=-12÷(-6)
Any expression divided by itself equals 1
c=-12÷(-6)
Dividing two negatives equals a positive
(-)÷(-)=(+)
c=12÷6
Calculate the quotient
c=2
Answer : 2
7) no solution